Silicon source from calcium silicate of steel making slag on leaf thickness, trichomes number, yield and silicon content in rice RD 49 variety grown under nutrient solution by deep water technique system - Srisuwan, Araya; Phommuangkhuk, Aunthicha; Amkha, Suphachai (Asia-Pacific Journal of Science and Technology, 2025)
Silicon (Si) is a beneficial element for plant growth, even though it is not considered an essential nutrient. Si plays a crucial role in strengthening plant structures, improving resistance to pests and diseases, and enhancing stress tolerance. The present study investigates the effects of calcium silicate from steel-making slag as a Si source on the plant growth, leaf thickness, number of trichomes, yield, and silicon content of rice (RD 49 variety) grown in a nutrient solution by the deep water technique. The experiment was conducted with a completely randomized design (CRD) with ten replications and nine treatments using nutrient solutions of 0.0, 0.1, 0.5, 1, 5, 10, 50, 100, and 500 mg CaSiO3/L. The results indicate that CaSiO3 concentrations of 10, 50 and 100 mg/L could promote rice growth and yield of rice. CaSiO3 concentrations of 50 and 100 mg/L effectively increased the cutin layer thickness. Additionally, the 100 and 500 mg/L CaSiO3 concentrations in the nutrient solution by the deep water technique were found to enhance the Si content in leaves, stem, and husk in rice. These findings suggest that CaSiO3 at concentrations of 50 and 100 mg/L can better promote a good yield and increased leaf thickness of rice (RD 49 variety) grown in a nutrient solution using the deep water technique.